ENGLISH TEACHER’S PROBLEMS IN IMPLEMENTING THE 2013 CURRICULUM IN ONLINE LEARNING AT SMA MUHAMMADIYAH BOARDING SCHOOL TARAKAN - Handayani, Rini; Ridwan, Ridwan (Borneo Journal of English Language Education, 2021)
Abstract The present study aimed at describing the English teacher’s problems in implementingthe 2013 curriculum in online learning at SMA Muhammadiyah Boarding SchoolTarakan. A case study was conducted to an English teacher at SMA MuhammadiyahBoarding School Tarakan. Data were collected through observation, interview, anddocumentation. The concurrent flows of analysis (data reduction, data display, andconclusion drawing) were used to reveal the English teaching problems. The result ofanalysis disclosed the problems from three teaching dimensions. In the preparation,the teacher found a hard struggling to compile the instructional documents because ofthe limitation of time in making the documents and in obtaining the references foronline learning. In the teaching and learning process, the teacher did not fully meetthe target of learning materials listed in the lesson plans because he had to adapt thematerials to the online class atmosphere. Controlling the students’ activities was alsothe challenging part during online class because the teacher could not see the studentsdirectly. Although, the teacher had mastered on how to use online learning platforms,some students could not use those platforms appropriately. The other problems wereunstable internet connection and support from students’ parents. These led thestudents became passive and decrease their motivation. In the assessment process, theteacher felt burdened because the assessment components were too complex. Besidesthat, there was a lot of tolerances given by the teacher to students.